Exploring Counternarratives to Linguistic Privileging and Invisibility: Community Translingualism as a Mechanism for Resourcefulness - Dobinson, Toni; Lamping, Sally; Dryden, Stephanie; Chen, Julian; Mercieca, Paul; Kuzich, Sonja (2025)
There is significant pressure on translingual communities, who draw upon and blend all the linguistic and semiotic resources with which they have come into contact (i.e., language, material objects, the built environment) to navigate linguistically inaccessible infrastructures in their new setting. We examined the role language plays within one Local Government Area (LGA) in Western Australia via a larger Critical Participatory Action Research (CPAR) project; re-visiting the politics of resourcefulness and focusing on examples of linguistic privileging and linguistic invisibility.